2019
DOI: 10.9775/kvfd.2018.21341
|View full text |Cite
|
Sign up to set email alerts
|

Çoklu Doymamış Yağ Asitleri ve Hayvansal Üretim Arasındaki İlişki: Derleme

Abstract: Polyunsaturated fatty acids (PUFAs) play important roles in maintaining normal physiological conditions and, consequently, in animal health. Two PUFAs families, n-6 and n-3 fatty acids (FAs), are physiologically and metabolically distinct. The focus on PUFAs has been gradually extended from the apparent properties of growth performance, antioxidant ability and immune function to the mechanism of molecular regulation and mechanism such as regulating the expression of related genes and the anticancer action mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…DHA is a key component of cellular membranes and is essential for maintaining the structure and function of the brain, exerting mostly anti-inflammatory effects [39]. On the other hand, adrenic acid, which belongs to the n-6 family and is a very minor component in animal tissues [40], was lower (p < 0.001) in the SBM diet than in the PS-L diet. Consequently, the n-6/n-3 ratio was higher in the PS-L diet than in the SBM diet, which would result in less favorable for human nutritional reasons [41].…”
Section: Behavior and Activity In Female Pigsmentioning
confidence: 99%
“…DHA is a key component of cellular membranes and is essential for maintaining the structure and function of the brain, exerting mostly anti-inflammatory effects [39]. On the other hand, adrenic acid, which belongs to the n-6 family and is a very minor component in animal tissues [40], was lower (p < 0.001) in the SBM diet than in the PS-L diet. Consequently, the n-6/n-3 ratio was higher in the PS-L diet than in the SBM diet, which would result in less favorable for human nutritional reasons [41].…”
Section: Behavior and Activity In Female Pigsmentioning
confidence: 99%
“…These FAs are known to alter immune cell functions as they change the makeup of cell membrane phospholipids to membrane lipid fluidity, signal transcription factors, and bioactive synthesis of lipid mediators. PUFAs along with maintaining cell structure and function also enhance immune functions, promote growth and maturity, and regulate lipid metabolism and related gene expression (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al. ( 2019 ) reported that polyunsaturated fatty acids included in the feed had an effect on the antioxidant metabolism of testicular tissue. Bas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al. ( 2019 ) reported that polyunsaturated fatty acids included in the feed of animals affect cellular functions and gene expression by playing an important role in the composition of membranes in cells, protecting haemostasis, affecting membrane fluidity, affecting cellular signalling processes and affecting cellular functions and gene expression. Jiang et al.…”
Section: Discussionmentioning
confidence: 99%